RC frames under earthquake loading : state of the art report. (T. Telford ; American Society of Civil Engineers, Publications Sales Dept. [distributor], 1996)
This report examines the behaviour of individual frame members subjected to the cyclic actions arising in seismically loaded frames i.e. slender flexure-dominated beams, short columns and beam-column joints. The report also considers global inelastic frame behaviour and its modelling, and the peculiarities of the behaviour of masonry-filled frames.